Does violent video games exposure reduce aggression? the moderating roles of self-esteem - Zaharim, Mohd Ziyad Afiq; Mohd Khir, Azlina; Md Noor, Amna; Borhan, Nik Ahmad Sufian (Human Resource Management Academic Research Society, 2023)
Media video games have become an integral part of peoples daily life. While previous studies have reported the detrimental outcomes of negative game factors, the impact of exposure to violent video games remains unclear. This study examined the effects of self-esteem in moderating the relationship between violent video games exposure and aggressive behavior. Data from 384 local online gamers in Klang Valley, Malaysia, were sampled using purposive and snowball sampling techniques and were analysed using SEM-PLS. The results demonstrate that self-esteem significantly moderates the relationship between violent video game exposure and aggressive behavior. This finding suggests that individuals with higher selfesteem may exhibit a weaker association between exposure to violent video games and subsequent aggressive behavior. These results shed light on the complex dynamics between game exposure, individual traits, and aggressive tendencies. Considering the questions raised by moderating analysis, future studies could investigate the impact of game factors in violent video games on aggressive behavior with a larger sample size.